Cost-benefits of grouper Epinephelus fuscoguttatus (Forsskål, 1775) stock enhancement and sea-ranching in Indonesia - Hammer, Cornelius (2021)
Stock enhancement and sea-ranching of groupers are a potential solution to overfishing of wild grouper catches. Hence, it is vital to understand the costs and benefits of stock enhancement and sea-ranching. A simulation was conducted to estimate the cost and benefits of using brown marbled grouper Epinephelus fuscoguttatus (Forsskål, 1775) for stock enhancement in the Karimunjawa Islands, Indonesia. The major costs for stock enhancement were the purchase of fish and transportation to the release site. Overall, the calculations of a theoretical benefit of 1.27–1.69 USD per released fish were estimated for the year 2017/2018 based on 1000 released fish of 10 and 15 cm length at release. The theoretical benefit decreased to 0.83 USD per released fish under extreme climate conditions exemplified by El Niño. Although releasing 15 cm E. fuscoguttatus was more costly and generated less economic benefit, the likelihood of predation for the larger fish was much lower. When the economic benefit of grouper mariculture is compared with stock enhancement, the former provides an additional advantage, which is conservatively estimated at 0.62 USD per individual. Besides, the annual benefit from the stock enhancement was estimated to be of 550,000 USD per year from related tourism activities in Karimunjawa Islands.